Ramadan Fasting and Feasting Illustrated! - Aljanahi, Muhanned Humaid; Afandi, Bachar O. (Journal of Diabetes and Endocrine Practice, 2024)
This vignette highlights the challenges faced by individuals with diabetes during Ramadan fasting and provides recommendations for effective management. The vignette presents the case of a 56-year-old man with type 2 diabetes who observes Ramadan fasting without seeking medical advice, resulting in poorly controlled blood glucose levels and associated symptoms. It underscores the importance of pre-Ramadan consultation, frequent blood glucose monitoring, and tailored management plans to address the unique needs of patients with diabetes during this religious observance.
Keywords: Ramadan fasting; diabetes; hyperglycemia; Ramadan feasting; continuous glucose monitoring